A Geographic Object-Based Image Approach Based on the Sentinel-2 Multispectral Instrument for Lake Aquatic Vegetation Mapping: A Complementary Tool to In Situ Monitoring - M. Tompoulidou; E. Karadimou; A. Apostolakis; V. Tsiaoussi (2024)
Tompoulidou Maria, Elpida Karadimou, Antonis Apostolakis, and Vasiliki Tsiaoussi. 2024. A Geographic Object-Based Image Approach Based on the Sentinel-2 Multispectral Instrument for Lake Aquatic Vegetation Mapping: A Complementary Tool to In Situ Monitoring. Remote Sensing 16(5): 916. https://doi.org/10.3390/rs16050916